Innovation Orientation in the Non-profit Sector: Analysis of Its Impact on the Performance of Spanish Non-governmental Development Organizations - Valero-Amaro, Víctor; Galera-Casquet, Clementina; Barroso-Méndez, María Jesús (Frontiers in Psychology, 2021)
Since 2015, the approval of the 2030 Agenda and of the 17 Sustainable Development Goals (SDGs) has led to a notable reshaping and expansion of the architecture of the international cooperation system. The SDGs mark a new path for the planning processes of the different actors working for development, expanding their goals, proposing an update of the roles they must play, and defining new frameworks for relationships and spaces for action. Non-governmental development organizations (NGDOs), whose traditional mission focused on reducing the poverty gap, defending human rights, or promoting environmental protection, must be able to respond satisfactorily to these new challenges, pass beyond their classic positions, and adapt to an increasingly complex and turbulent global context. Achieving high impact in the SDGs requires development organizations to be more agile and innovative. With the intention of bringing visibilty to the importance that innovation can play in the success and results achieved by development cooperation organizations, the main objective of this study was to validate, through a sample of Spanish NGDOs, a causal model that represents the positive contribution which innovation orientation generates in the result of the activity of these entities. This research concludes by confirming that innovation orientation favours the attainment of a higher degree of success in the projects and actions carried out by non-profit entities which promote the SDGs, which has a direct and positive impact on the performance they achieve.